Productivity and market participation of Fluted pumpkin farmers under tropical conditions (2020)
Increased productivity and participation of farmers in the market are pertinent for improved farm incomes. Factors affecting participation for Fluted Pumpkin (Telfaria occidentalis Hook F.) are lacking. Factors influencing productivity and market participation among 200 Fluted Pumpkin farmers were examined. An ordinary least squares regression model indicated farm size, use of seed of improved varieties, and years of education, positively influenced productivity; quantity of seed and fertilizer use negatively influenced productivity. Most farmers were productive. Fluted pumpkin farmers participated in the market to a high degree. Improved participation of farmers in the market appears to be based on gender, marital status, level of education and market experience. Drivers of productivity and participation of Fluted pumpkin farmers are important for enhanced, sustainable, production, to meet increasing demand and exploring the potential as an exportable crop.